2019
DOI: 10.1111/os.12430
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted Percutaneous Cannulated Screw Fixation of Femoral Neck Fractures: Preliminary Clinical Results

Abstract: Objective To assess the clinical efficacy of TiRobot‐assisted percutaneous cannulated screw fixation in the treatment of femoral neck fractures. Methods From September 2015 to July 2017, 26 patients with unilateral femoral neck fractures were treated with TiRobot‐assisted percutaneous cannulated screw fixation. The femoral necks were fixed using three cannulated screws with robot assistance applying the following procedure: image acquisition, path planning, and needle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
101
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(107 citation statements)
references
References 21 publications
5
101
1
Order By: Relevance
“…The screw parallelism was significantly improved and the neck‐width coverage was significantly enlarged compared to the conventional surgery group. However, there was no significant difference between the two groups in terms of the fracture healing rate and Harris scores at the last follow‐up 10 .…”
Section: Introductionmentioning
confidence: 74%
“…The screw parallelism was significantly improved and the neck‐width coverage was significantly enlarged compared to the conventional surgery group. However, there was no significant difference between the two groups in terms of the fracture healing rate and Harris scores at the last follow‐up 10 .…”
Section: Introductionmentioning
confidence: 74%
“…Due to variation in the anatomical shape of the femoral neck, the cannulated screw configuration and steel plate size should be individually selected according to the shape of the femoral neck on the healthy side before surgery. Precise preoperative planning aided by computer stimulation or 3D‐print may be a trend in the treatment of femoral neck fractures in the future 12,33 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the important factors that affect the implant selection and mechanical properties of femoral neck internal fixation is the spatial shape of the femoral neck canal, especially the morphological characteristics of the cross‐section of the femoral neck isthmus, which directly affects both the spatial configuration and type of the cannulated screws 7 . Previous studies have shown that the cross‐section of the femoral neck gradually changed from a circle to an oval shape from the proximal to distal ends 11,12 . Du et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations